Research through Design as a transformative approach - Vilja Larjosto (Räumliche Transformation: Prozesse, Konzepte, Forschungsdesigns, 2019)
New and experimental research methods to understand and co-steer processes of spatial transformation are called for. From the perspective of designing urban landscapes this paper draws a connection between Research through Design and transformative science. (Urban) landscapes constantly undergo (spatial) transformation, and not only have landscape architects always dealt with perpetual change, they increasingly often catalyze it. Designing is an integrative activity and the central means of the discipline to understand issues and draw up possible solutions. Furthermore, design often reaches out to other disciplines, involves multiple participants, and can be paradigm shifting. Research through Design is an increasingly acknowledged approach in landscape architectural research. With regard to the procedures, characteristics and goals of knowledge production, this paper presents commonalities between Research through Design and transformative research, highlighting the integrative and projective nature of designing. In conclusion, I suggest positioning Research through Design among the methods of transformative research. – – Um Prozesse der räumlichen Transformation zu verstehen und zu steuern, sind neue und experimentelle Forschungsmethoden notwendig. Aus der Perspektive der Gestaltung urbaner Landschaften stellt dieser Beitrag eine Verbindung zwischen entwerfender Forschung - Research through Design - und transformativer Wissenschaft dar. (Urbane) Landschaften befinden sich in permanenter (räumlicher) Transformation. Landschaftsarchitekten setzen sich daher nicht nur mit deren Veränderungen auseinander, sondern katalysieren diese auch. Das Entwerfen stellt somit eine integrative Tätigkeit und die zentrale Vorgehensweise der Disziplin dar, um Themen zu verstehen und Lösungsansätze zu erarbeiten. Entwurfsprozesse erstrecken sich daher oft auch auf andere Disziplinen, integrieren verschiedenste Akteure und können Paradigmenwechsel fördern. In der landschaftsarchitektonischen Forschung ist Research through Design ein innovativer Ansatz. Im Hinblick auf die Vorgehensweisen, Eigenschaften und Ziele der Wissensproduktion stellt dieser Beitrag Gemeinsamkeiten zwischen entwerfender Forschung und transformativer Forschung dar und hebt den integrativen, bereichernden Charakter des Designs hervor.
urn:nbn:de:0156-0891170; hdl:10419/204438; https://econpapers.repec.org/RePEc:zbw:arlfob:10
Keywords: 710; Research through Design; urban landscape; spatial transformation; transformative research; integrative method; Entwerfende Forschung; urbane Landschaft; räumliche Transformation; transformative Forschung; integrative Methode